Extracts from the letters and journals of George Fletcher Moore ... : now filling a judicial office at the Swan River Settlement - Moore, George Fletcher, 1798-1886.; Doyle, Martin (London : Orr and Smith ; Dublin : W. Curry, Jun., 1834)
Swan R. Settlement; Conflicts with natives; Physical appearance; King Georges Sound intertribal conflict; Killing of person of another tribe if one dies to preserve balance of power; Hair dressed with grease and red ochre; p.101; Note of rock painting; p.224; Description of kangaroo dance by King Georges Sound natives.
Ferguson, J.A. Bibliography of Australia
Keywords: Frontier and pioneer life -- Western Australia; Voyages and travels; Stories and motifs - Kangaroos / Wallabies; Art - Rock art - Painting; Costume and clothing - Hair dressing; Art - Rock art - Conservation; Human biology - Physical anthropology - Hair characteristics; Swan River (SW WA SH50-14)